GPS enabled embedded veichle speed limiting device for electric veichles - Suman, Maloji; Gopi Krishna, P; V.S. Kasyap, D; Harika, K (International Journal of Engineering and Technology, 2018)
Many of the accidents are caused due to the over speed of the vehicles. The vehicle user’s drive above the speed limit in speed restricted areas. According to the statistics, in India there are more than 1,00,000 fatal crashes per year. With various implantations the numbers of accidents have been decreasing. The speed of the vehicle is prevented by the implementations. One of such implementations is to control the speed by using GPS. The aim of this paper is to design an embedded system that automatically control speed of the vehicle based on its location determines by GPS module. The system will make use of Arduino micro controller connected to the GPS module which is connected to GPS antenna. The GPS antenna is used to determine the latitudes and longitude of the vehicle. The latitude and longitude are displayed on the LCD display. A gear motor is connected to Arduino which receives the information from GPS antenna. The system output will be determined from the Engine Control Unit (E.C.U). Each zone is limited at a certain speed. Whenever the vehicle enters into that zone the speed is controlled by controlling the RPM so that the over speed will be reduced to a desired speed limit.